Frequency Regulation of Distribution Networks Using Grid-Forming Inverter with Virtual Synchronous Generator Control - Hara, Marisivilai; Srirattanawichaikul, Watcharin (Thailand Electrical Engineering Journal (TEEJ), 2025)
The problem caused by the increasing share of renewable energy sources (RES) in the grid is the reduction of inertia. Inertia in a grid comes only from synchronous generators and is essential for maintaining power balance by responding to sudden changes. This article presents a control method for RES inverters to create virtual inertia, known as a virtual synchronous generator (VSG). Simulation results show that when the grid becomes unbalanced due to a sudden load increase, the VSG responds quickly and adjusts its output power to meet the load. As a result, the grid frequency stays within the acceptable range. These results show that the VSG can maintain frequency stability in grids with a high share of RES.